Habitat characterization of Amoreuxia wrightii (Bixaceae), a species of Northeastern Mexico at risk - Soto-Mata, Brianda; Alanís Rodríguez, Eduardo; Jurado, Enrique; Pando-Moreno, Marisela; Molina-Guerra, Víctor; Alcalá-Rojas, Alejandro; Marroquín-Castillo, Jonathan J. (Instituto de Ecología, A.C., 2018)
Background and Aims: In Mexico, Amoreuxia wrightii is endangered according to NOM-059-SEMARNAT-2010. In this study the characterization of natural populations of A. wrightii, which grow in two contrasting communities taking into account the canopy cover in the Tamaulipan thornscrub in northeastern Mexico, was performed by analysis of associated flora and physical and chemical properties of soils.Methods: In 2014, 10 sampling sites were established in two environments differentiated by vegetation structure: five sites in plant associations with dense vegetation cover and five sites in disturbed areas with bare soil. In each area the vegetation structure and edaphic variables were evaluated and a Canonical Correspondence Analysis was performed.Key results: According to the relationship with other species, A. wrightii was associated with pioneer species that emerge after disturbance, dominated by grasses like Aristida purpurea, Cenchrus ciliaris, Cynodon dactylon, Panicum obtusum, herbs such as Gutierrezia sarothrae, Gymnosperma glutinosum and Parthenium hysterophorus, and low shrubs like Acacia amentacea, A. berlandieri and Eysenhardtia texana. According to edaphic variables, it was observed that A. wrightii preferred clayey and silty soils, soils with slightly alkaline pH and high bulk density. No individual of A. wrightii was recorded at sites that had soils with high sand content and high content of organic matter.Conclusions: Amoreuxia wrightii was more abundant in areas with no coverage, devoid of vegetation, soils low in organic matter and high in pH, silt, clay and bulk density. According to the relationship with other species, it was associated with pioneer species, which emerge after a disturbance.